Association between chemotherapy and disease-specific survival in women with borderline ovarian tumors: A SEER-based study. (November 2019) - Wang, Yichen; Sun, Haiyan; Yu, Aijun; Zhu, Tao; Chen, Xi
Abstract: Background: The impact of chemotherapy on disease-specific survival in patients with borderline ovarian tumors (BOTs) has not been studied previously. Methods: Patients with BOTs were identified from The Surveillance, Epidemiology, and End Results (SEER) database. Associations of chemotherapy and other risk factors with disease-specific survival were analyzed using Cox proportion hazards regression models. Results: A total of 6065 patients diagnosed during 1988–2000 were selected. The mean age at diagnosis was 48.0 ± 16.5 with a median follow-up time of 190.0 ± 72.5 months. The majority of BOTs were at stage I (86.7%) and treated with surgery (99.3%). Chemotherapy and radiotherapy were given to 343 patients (5.7%) and 33 (0.5%) patients, respectively. A total of 296 patients (4.9%) died from this disease. Both univariate and multivariate survival analysis showed that chemotherapy, older age, bilateral tumor, advanced stage, non-surgery and radiotherapy were associated with worse disease-specific survival. The comprised effect of chemotherapy remained after patients were stratified by age, histology and stage. Conclusions: Chemotherapy is associated with worse disease-specific survival in patients with BOTs. Tumor laterality, age, stage and other treatments are also prognostic factors for this disease.